IMPEDANCE CHARACTERISTICS of La3/2Bi3/2Fe5O12 CERAMICS - Jawahar, K.; Behera, Banarji [UNESP]; Choudhary, R. N. P. (World Scientific Publ Co Pte Ltd, 2009)
Polycrystalline La3/2Bi3/2Fe5O12 (LBIO) compound was prepared by a high-temperature solid-state reaction technique. The complex impedance of LBIO was measured over a wide temperature (i.e., room temperature to 500 C) and frequencies (i.e., 10(2)-10(6) Hz) ranges. This study takes advantage of plotting ac data simultaneously in the form of impedance and modulus spectroscopic plots and obey non-Debye type of relaxation process. The Nyquist's plot showed the presence of grain effects in the material at high temperature. The ac conductivity spectrum was found to obey Jonscher's universal power law. The dc conductivity was found to increase with rise in temperature. The activation energy of the compound was found to be 0.24 and 0.51 eV in the low and high-temperature region, respectively, for conduction process.
Keywords: Impedance; Nyquist's plots; ac conductivity; dc conductivity